School facilities, Parental Subject Perception and Teachers’ Professionalism as Correlates of Students’ Learning Outcome in Agricultural Science in Bayelsa State (2018)
Students' poor performance in science generally and Agricultural science in particular has been considered a serious problem in senior secondary school education by the major stakeholders in spite of various governmental efforts and instructional resources employed in the classroom to teach. The study carried out empirical investigation on school facilities, parental subject perception and teachers' professionalism as correlates of students' learning outcome in Agricultural Science. Four research questions that were raised and answered. This study adopted survey design of correlational type. Purposive sampling technique was used to sample 40 SS2 students per school and 400 parents of agricultural students as well as 20 teachers giving a total of 820 respondents. The three independent variables include school facility, parent subject perception and teachers’ professionalism while the dependent variable is student learning outcome in Agricultural Science. The four instruments for data collection are: School Facilities Inventory (SF!) (r=0.86), Teachers' Professionalism Questionnaire (TPQ), (r=0.71), Parental Subject Perception Questionnaire (PSQ) (r =0.76) and Agricultural Science Achievement Test (ASAT) with reliability coefficient of 0.83. Inferential statistics was used to analyse the data collected. Results revealed a positive and negative significant relationship among the predictors (School Facility (r = .0.248, p< 0.05), Parental Subject Perception (r a -.0.244, p< 0.05) and Teachers' Professionalism (r = .0.250, p<0.05). Moreover, there is a positive multiple correlation among the three predictors(R = 0.343). Also, the model was found to be statistically significant (F 0, 3%) = 17.651, p < 0.05). It is therefore recommended that teachers should ignite student interest and increase student motivation to learn by making connections between what the students are learning and what is going on in their own lives.